2014
DOI: 10.1039/c4cp02503b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of synergistic Cu/V redox pair in VCu:AlPO-5; a comparison with VCu:ZSM-5

Abstract: Vanadium(V) and copper(II) were co-deposited into AlPO-5 and H-ZSM-5 three-dimensional microporous carriers to yield VCu:AlPO-5 and VCu:ZSM-5. The materials, along with copper analogues were tested for the selective oxidation of propene, and the catalysts perform in the following order: VCu:AlPO-5 > Cu:AlPO-5 > VCu:ZSM-5 > Cu:ZSM-5. Acrolein was selectively formed over VCu:AlPO-5 and Cu:AlPO-5 over a very wide range from 300 to 450 °C, whereas VCu:ZSM-5 displays a limited temperature window for acrolein format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…It is conductive to the formation of oxygen vacancies as well as the reduction of the terminal VO and bridging V–O–V bond strength, which is a key parameter in the surface dehydrogenation and product desorption steps. Bøyesen et al have confirmed the existence of V–O–Cu at VCu:AlPO-5 by X-ray absorption near-edge structure (XANES) . Thus, we suggest that the formation of V–O–Cu from the synergy between VO x and Cu leads to the red shift and weaken VO and V–O–V bonds.…”
Section: Resultssupporting
confidence: 67%
“…It is conductive to the formation of oxygen vacancies as well as the reduction of the terminal VO and bridging V–O–V bond strength, which is a key parameter in the surface dehydrogenation and product desorption steps. Bøyesen et al have confirmed the existence of V–O–Cu at VCu:AlPO-5 by X-ray absorption near-edge structure (XANES) . Thus, we suggest that the formation of V–O–Cu from the synergy between VO x and Cu leads to the red shift and weaken VO and V–O–V bonds.…”
Section: Resultssupporting
confidence: 67%
“…Microwave and additives are used to help H 2 O 2 solution perform desulfurization and denitrification simultaneously. Some researchers in other countries use sodium hypochlorite and potassium permanganate to form a new type of absorbent that has a high absorption efficiency for SO 2 and NO. The oxidation reaction experiments are performed by loading V and Cu, between which a certain synergy exists. , For the collaborative desulfurization and denitrification of the dust collector, some researchers established a 1D fluid model of simultaneous desulfurization and denitrification through a negative DC corona discharge, which is similar to an electrostatic precipitator (ESP). The nonthermal plasma produced by corona discharge has a significant effect on the removal of SO 2 and NO in flue gas …”
Section: Introductionmentioning
confidence: 99%
“…The oxidation reaction experiments are performed by loading V and Cu, between which a certain synergy exists. 25,26 For the collaborative desulfurization and denitrification of the dust collector, some researchers established a 1D fluid model of simultaneous desulfurization and denitrification through a negative DC corona discharge, which is similar to an electrostatic precipitator (ESP). The nonthermal plasma produced by corona discharge has a significant effect on the removal of SO 2 and NO in flue gas.…”
Section: Introductionmentioning
confidence: 99%